2017
DOI: 10.3847/1538-4357/aa5c37
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Anomalous Microwave Emission with Spinning Nanoparticles: No PAHs Required

Abstract: In light of recent observational results indicating an apparent lack of correlation between the anomalous microwave emission (AME) and mid-infrared emission from polycyclic aromatic hydrocarbons, we assess whether rotational emission from spinning silicate and/or iron nanoparticles could account for the observed AME without violating observational constraints on interstellar abundances, ultraviolet extinction, and infrared emission. By modifying the SpDust code to compute the rotational emission from these gra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
99
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 67 publications
0
99
4
Order By: Relevance
“…The leading explanation for AME is rotational emission from ultra-small (a 1 nm) dust grains (i.e., "spinning dust"), which was first postulated by Erickson (1957). In this model, rapidly rotating very small grains with non-zero electric dipole moments produce the ob-served microwave emission (Draine & Lazarian 1998;Planck Collaboration et al 2011;Hensley & Draine 2017). Magnetic dipole radiation from thermal fluctuations in the magnetization of interstellar dust grains (Draine & Lazarian 1999;Draine & Hensley 2013), may also be contributing to observed AME, particularly at higher frequencies ( 50 GHz).…”
Section: Introductionmentioning
confidence: 99%
“…The leading explanation for AME is rotational emission from ultra-small (a 1 nm) dust grains (i.e., "spinning dust"), which was first postulated by Erickson (1957). In this model, rapidly rotating very small grains with non-zero electric dipole moments produce the ob-served microwave emission (Draine & Lazarian 1998;Planck Collaboration et al 2011;Hensley & Draine 2017). Magnetic dipole radiation from thermal fluctuations in the magnetization of interstellar dust grains (Draine & Lazarian 1999;Draine & Hensley 2013), may also be contributing to observed AME, particularly at higher frequencies ( 50 GHz).…”
Section: Introductionmentioning
confidence: 99%
“…Hoang et al (2016) and Hensley & Draine (2017a) argued that the so-called "anomalous microwave emission" (AME), an important Galactic foreground of the cosmic microwave background radiation in the ∼ 10-100 GHz region, could arise from spinning nano-sized silicate grains. However, silicate nanoparticles will undergo single-photon heating in the ISM and emit at the 9.7 µm Si-O feature.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that this is not always the case, and that AME correlates better with the total far-infrared radiance than with the Planck 353 GHz optical depth (Hensley et al 2016). This result was taken as evidence that polycyclic aromatic hydrocarbons (PAHs) are not necessarily the dominant source of spinning grain emission, and that instead nanosilicates (with a minor contribution from iron nanoparticles) could be responsible for the bulk of AME (Hensley & Draine 2017). Specifically for the Crab, we do not find a correlation between the dust mass column density (see Fig.6, bottom left panel) and the location of the mm excess emission (see Fig.8, right column).…”
Section: Appendix D: Alternative Explanations For the MM Excess Emissmentioning
confidence: 99%